Development of the “Bon Voyage!” Board Game Media for French Culture Learning - Chika Hana Lestari; Yadi Mulyadi; Farida Amalia (Raja Zulkarnain Education Foundation, 2026)
Foreign language learning cannot be separated from cultural learning, as language reflects the values, norms, and social practices of its speakers. In French language learning in Indonesia, particularly in the Civilisation Française course, students often experience difficulties in understanding cultural materials that are complex and chronological, such as history, political systems, historical sites, and French traditions. These difficulties are also influenced by teacher-centered learning methods and the limited variety of instructional media, which results in low student interest and learning motivation. This study aims to develop a game-based learning medium in the form of a board game entitled “Bon Voyage!” as an alternative medium for learning French culture and to determine the validity and feasibility of the developed media. This study employs a Research and Development (R&D) method using the PPE (Planning, Production, and Evaluation) model. The Planning stage includes needs analysis and media design, the Production stage involves the development of the game board, culture cards, instruction manual, and supporting components, while the Evaluation stage is conducted through validation by subject-matter and media experts. The research instrument consists of validation sheets using a four-point Likert scale (1–4), and the data are analyzed quantitatively using percentage techniques. The results show that the “Bon Voyage!” board game achieved a feasibility percentage of 97.50% in the material aspect and 90.00% in the media aspect, both of which fall into the “very feasible” category. Therefore, the “Bon Voyage!” board game is considered valid and feasible for use as a learning medium in the Civilisation Française course.